Human extracellular superoxide dismutase (EC-SOD) expression in transgenic chicken - Byun, Sung June (Korean Society for Biochemistry and Molecular Biology, 2013)
Extracellular superoxide dismutase (EC-SOD) is a metalloprotein and functions as an antioxidant enzyme. In this study, we used lentiviral vectors to generate transgenic chickens that express the human EC-SOD gene. The recombinant lentiviruses were injected into the subgerminal cavity of freshly laid eggs. Subsequently, the embryos were incubated to hatch using phases II and III of the surrogate shell ex vivo culture system. Of 158 injected embryos, 16 chicks (G0) hatched and were screened for the hEC-SOD by PCR. Only 1 chick was identified as a transgenic bird containing the transgene in its germline. This founder (G0) bird was mated with wild-type hens to produce transgenic progeny, and 2 transgenic chicks (G1) were produced. In the generated transgenic hens (G2), the hEC-SOD protein was expressed in the egg white and showed antioxidant activity. These results highlight the potential of the chicken for production of biologically active proteins in egg white. [BMB Reports 2013; 46(8): 404-409]